Intellectual Property as an Object of Banks Collateral in Startup Development in Indonesia (Comparation Study of Singapore and Malaysia) - Giovanni Marcello; Rafi Rifal Mastiyanto (Journal of Private and Commercial Law, 2023)
Startups heavily rely on capital for their business activities, often acquired through borrowing. Securing capital loans with guarantees is vital to ensure repayment. Intellectual Property Rights (IPR) offer valuable intangible assets that can serve as collateral. However, Indonesia's current regulations on using IPR as collateral, particularly in debt financing, are insufficient. In contrast, Singapore and Malaysia successfully implemented the Intellectual Property Financing Scheme (IPFS). This paper examines a regulatory model for implementing IPFS in Indonesia. It explores how to effectively utilize intellectual property schemes as debt guarantees in Indonesia, Singapore, and Malaysia. The author uses the normative juridical research method for this study. The analysis concludes that IPFS is a viable solution for Indonesia if two key indicators are met. First, a due diligence scheme for intellectual property assets must be developed and optimized to ensure reliable and valuable collateral. Second, implementing a nationally integrated Government Program to optimize startup capital will support the successful adoption of IPFS in Indonesia. By establishing a robust regulatory model and embracing IPFS, Indonesia can harness the potential of its intellectual property assets to boost startup capital and encourage business growth. This will improve financing accessibility for startups and foster an environment conducive to innovation and entrepreneurship in the country.